A basin-scale inventory and hydrodynamics of floodplain wetlands based on time-series of remote sensing data. Issue 1 (2nd January 2022) - Singh, Manudeo; Sinha, Rajiv
ABSTRACT: The world is rapidly losing its wetlands. To contain the loss, the first and foremost requirement is to prepare an inventory of wetlands based on historical datasets. Individual wetlands in a catchment system are not standalone entitites, and together, they control the hydrological processes of the catchment. Therefore, it is essential to map the wetlands at the catchment scale to understand their relationship with the adjoining water bodies. This will further help to develop sustainable strategies for their revival and management. In the present work, we have formulated a simple yet robust method to (a) map the wetlands and (b) document surface dynamics of wetlands by applying pixel-scale binary logic (wet/not-wet) to the time-series Landsat dataset. We have applied this method to a large basin in the Ganga Plains and mapped a total of 3226 wetlands in the basin. The method can also be applied to map wetlands at a pixel scale to a basin scale.